The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jms.734
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience and accelerator mass spectrometry

Abstract: Accelerator mass spectrometry (AMS) is a mass spectrometric method for quantifying rare isotopes. It has had a great impact in geochronology and archaeology and is now being applied in biomedicine. AMS measures radioisotopes such as 3 H, 14 C, 26 Al, 36 Cl and 41 Ca, with zepto-or attomole sensitivity and high precision and throughput, allowing safe human pharmacokinetic studies involving microgram doses, agents having low bioavailability or toxicology studies where administered doses must be kept low (<1 µg k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In the last decade, AMS has emerged as a sensitive tool for bioanalytical tracing. Reviews on the use of AMS in neuroscience 8 and phytochemical research 9 highlighted the possibility of quantifying isotopes at the 1 in 10 15 level. This corresponded to zepto-to attomoles of isotopically labelled compounds in mg to mg amounts of sample.…”
Section: Reviewsmentioning
confidence: 99%
“…In the last decade, AMS has emerged as a sensitive tool for bioanalytical tracing. Reviews on the use of AMS in neuroscience 8 and phytochemical research 9 highlighted the possibility of quantifying isotopes at the 1 in 10 15 level. This corresponded to zepto-to attomoles of isotopically labelled compounds in mg to mg amounts of sample.…”
Section: Reviewsmentioning
confidence: 99%
“…)[72]. The pesticide exposures significantly increased the amount of DFP, a miotic pharmaceutical often used as a research analog of organophosphate pesticides and nerve agents, bound to the cholinesterase in the brain, suggesting a possible link between cholinergic pesticide exposure and increased susceptibility to very low amounts of nerve agents among certain troops after destruction of nerve gas depots [73-74]. The study further demonstrated that daily doses of the protective transient cholinesterase inhibitor, pyridostigmine bromide, sub-chronically dosed at 50 μg/kg prior to 14 C-DFP administration, produced a significant 15% decrease in brain-bound DFP.…”
Section: Drug-drug and Drug-environment Interactions: Co-administementioning
confidence: 99%
“…The cells in the cortex of the adult human brain have been investigated, and it was found that while non-neuronal cells are replaced, occipital neurons are as old as the individual (Spalding et al, 2005;Bhardwaj et al, 2006). The AMS measurements for these investigations (Palmblad et al, 2005) were performed at the Lawrence Livermore National Laboratory. 14 C levels from samples containing as little as 30 mg carbon were analyzed (corresponding to genomic DNA from 15 million cells), thus taking advantage of the full potential of the AMS method.…”
Section: Some Specific Applicationsmentioning
confidence: 99%